'Hospice inpatient deep vein thrombosis detection (HIDDen) in advanced non-malignant diseases': a longitudinal pilot study. Issue Volume 12:Issue e6(2022) (11th February 2020) - White, Clare; Noble, Simon; Swan, Flavia; Watson, Max; Allgar, Victoria; Napier, Eoin; Nelson, Annmarie; Johnson, Miriam J
Abstract : Objectives: To gain preliminary data regarding the prevalence of proximal deep vein thrombosis (DVT) in those with non-malignant conditions admitted to specialist palliative care units (SPCUs). Methods: Data were collected as part of a prospective longitudinal observational study in five SPCUs in England, Wales and Northern Ireland (Registration: ISRCTN97567719 ) to estimate the prevalence of proximal femoral vein DVT in people admitted to SPCUs. The primary outcome for this exploratory substudy was the prevalence of DVT in patients with non-malignant palliative conditions. Consecutive consenting adults underwent bilateral femoral vein ultrasonography within 48 hours of admission. Data were collected on symptoms associated with venous thromboembolism. Patients were ineligible if the estimated prognosis was <5 days. Cross-sectional descriptive analysis was conducted on baseline data and prevalence estimates presented with 95% CIs. Results: 1390 patients were screened, 28 patients had non-malignant disease and all were recruited. The mean age 68·8 (SD 12·0), range 43–86 years; men 61%; survival mean 86 (SD 108.5) range 1–345 days. No patient had a history of venous thromboembolism. Four (14%) were receiving thromboprophylaxis. Of 22 evaluable scans, 8 (36%, 95% CI: 17% to 59%) showed femoral vein DVT. The level of reported relevant symptoms (leg oedema, leg pain, chest pain and breathlessness) was high irrespective of the presence of DVT. Conclusions: Our exploratory data indicate one in three people admitted to an SPCU with non-malignant disease had a femoral vein DVT. Although definitive conclusions cannot be drawn, these data justify a larger prospective survey.